Contribution of Law Enforcement Institutions in Protecting Street Children’s Rights in Dar Es Salaam, Tanzania - Emanuel E. Chingonikaya; Farida S. Salehe (Archives of Current Research International, 2019)
Tanzania is one of the countries which have ratified the UN Convention on the Rights of the Child which means they are committed to protecting the rights of all children. Moreover, over 50% of the population of Tanzania is aged 18 years and under, the need to invest in the development and protection of children becomes more important. There is an increasing number of street children in many cities in Tanzania. The reasons for causing street children are widely known. There are law enforcement institutions for protecting children. However, it is not widely known on the contribution of these institutions in protecting street children rights. The study determined the contribution of law enforcement institutions in protecting Street children's rights. Specific objectives of the research were to examine the roles of law enforcement institutions in protecting children's rights at various levels of the society and determine the community's attitude towards violation of children’s rights. The study was conducted in Temeke and Ilala municipalities in Dar es Salaam city. A cross-sectional research design was adopted. A representative sample of 120 street children was used. Both primary and secondary data were collected. A questionnaire survey, focus group discussion, key informant interview and personal observation methods were used to collect the primary data. The Statistical Package for Social Science (SPSS) for Windows Version 12.0 was used for data analysis. Results of this study revealed that some of the street children's rights for protection were being violated by various law enforcement institutions. From the perspective of communities, many of them regarded the street children as criminals. The study concludes that many street children to get the rights for protection. From the findings, it is recommended that law enforcement institutions should not always use forces due to the notion that street children are criminals.